PENINGKATAN MINAT BACA ANAK ANAK DESA SIHARANG-KARANG MELALUI KEGIATAN MOTIVASI DAN PEMBERIAN BAHAN BACAAN - Rizki Tridamayanti Siregar; Dian Lestari Siregar; Murni Kurnianti Siregar; Anggia Dasa Putri; Raymond (LPPM-Universitas Batam, 2024)
This community service activity aims to increase children's interest in reading in Siharak Karang. The activity method consists of providing motivation and providing reading materials in the form of reading books, picture books and stationery. Apart from that, participants are also asked to write down the main messages that can be obtained from reading books. The results of this activity resulted in an increase in interest in reading and the conclusion from this activity was that the activity participants wanted the activity to be carried out in a more structured way to develop children's interest in reading.